Budgeting and Bookkeeping Assistance for MSMEs Women Entrepreneurs in Banguntapan, Bantul, Yogyakarta: Pendampingan Penganggaran dan Pembukuan pada Pengusaha Wanita UMKM Banguntapan, Bantul, Yogyakarta - Paramitalaksmi, Ratri; Airawaty, Diana (Yayasan Ahmar Cendekia Indonesia, 2023)
This community service aims to provide education on budgeting and order in the preparation of good MSME financial statements. Our partners in this charity activity are PKK mothers from Padukuhan Mertsanan Kulon, Banguntapan, Bantul. These PKK members are housewives with relatively low income and educational background, so their awareness of financial reporting and budgeting tends to be considered trivial and confusing. But actually these PKK members run various types of simple MSMEs such as laundry, bakery, and others, although the management has not been improved. The problem is that entrepreneurship is still unstable (can suddenly quit a job), and the budget (finance) and accounting systems do not yet exist. The strategies and techniques used in this community service include entrepreneurship presentations and budgeting and accounting training. The results achieved were entrepreneurship and understanding of budget (finance) and accounting systems to support various types of MSME business activities owned by PKK members from Padukuhan Mertsanan Kulon, Banguntapan, Bantul, Yogyakarta.